2016
DOI: 10.1097/rhu.0000000000000363
|View full text |Cite
|
Sign up to set email alerts
|

Is Bariatric Surgery a Trigger Factor for Systemic Autoimmune Diseases?

Abstract: Bariatric procedures are an effective option for weight loss and control of comorbidities in obese patients. Obesity is a proinflammatory condition in which some cytokines such as leptin, a proinflammatory protein, is elevated and adiponectin, an anti-inflammatory protein, is decreased. In patients undergoing weight reduction surgeries, these hormone levels behave paradoxically. It is not known whether bariatric surgery protects against development of autoinflammatory or autoimmune conditions; nevertheless, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Bitarafan et al reported four patients who developed MS after severe intentional weight loss, which was attributed to result from an inflammatory process. 7 Furthermore, four patients have been reported to develop systemic lupus erythematosus and rheumatoid arthritis, which are autoimmune diseases, after significant weight loss 20 Our case series is consistent with these findings since all our patients were diagnosed with MS, which is also an autoimmune disease, after an average of two years of undergoing different bariatric surgeries.…”
supporting
confidence: 88%
“…Bitarafan et al reported four patients who developed MS after severe intentional weight loss, which was attributed to result from an inflammatory process. 7 Furthermore, four patients have been reported to develop systemic lupus erythematosus and rheumatoid arthritis, which are autoimmune diseases, after significant weight loss 20 Our case series is consistent with these findings since all our patients were diagnosed with MS, which is also an autoimmune disease, after an average of two years of undergoing different bariatric surgeries.…”
supporting
confidence: 88%
“…Recently, there have been case reports of patients developing CD following bariatric surgery . Interestingly, there have also been reports of immune‐mediated diseases occurring after weight loss surgery . In order to explore the possible relationship between bariatric surgery and IBD, we first compiled a multicentre descriptive case series.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] Interestingly, there have also been reports of immune-mediated diseases occurring after weight loss surgery. 15 In order to explore the possible relationship between bariatric surgery and IBD, we first compiled a multicentre descriptive case series. We subsequently examined the association between prior bariatric surgery and risk of new-onset IBD in a large health claims database.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of weight loss on the immune system is still controversial and even more when weight loss can be massive and fast. In a previous article by our group, we described the development of autoimmune diseases following weight loss associated with bariatric surgery [ 2 ]. In addition, some cases reported in the world literature have shown that a marked decrease in body mass index (BMI) might possibly trigger autoimmunity-related rheumatologic syndromes and metabolic processes resulting mainly from rapid weight loss [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous article by our group, we described the development of autoimmune diseases following weight loss associated with bariatric surgery [ 2 ]. In addition, some cases reported in the world literature have shown that a marked decrease in body mass index (BMI) might possibly trigger autoimmunity-related rheumatologic syndromes and metabolic processes resulting mainly from rapid weight loss [ 2 ]. Currently, the effects of bariatric surgery on the immune system, including the different T and B cell subpopulations, autoantibodies, complement and markers of inflammatory activity are unknown.…”
Section: Introductionmentioning
confidence: 99%